2004
DOI: 10.1097/01.ju.0000144505.40915.98
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer as a Prognostic Factor for Upper Tract Transitional Cell Carcinoma

Abstract: This study demonstrates that a history of BTCC (invasive or superficial) has an adverse effect on the prognosis of patients diagnosed with UTTCC independent of primary tumor stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
4
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 14 publications
3
45
4
7
Order By: Relevance
“…5,8,[10][11][12][13][15][16][17]20,22,24,25 Regarding pT3 pelvic cancer, our data demonstrating significantly poorer outcome of patients with UCs showing macroscopic parenchyma and/or fat invasion compared with patients with UCs showing microscopic parenchyma invasion only are in line with two previous studies. 35,36 They reported that pT3 UCs with extensive parenchymal invasion (defined as invasion deeper than 5 mm) had a prognosis similar to that of pT4 tumors, whereas pT3 UCs without extensive parenchymal invasion (including cases with intraductal spread only) had a prognosis similar to that of pT1/pT2 disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…5,8,[10][11][12][13][15][16][17]20,22,24,25 Regarding pT3 pelvic cancer, our data demonstrating significantly poorer outcome of patients with UCs showing macroscopic parenchyma and/or fat invasion compared with patients with UCs showing microscopic parenchyma invasion only are in line with two previous studies. 35,36 They reported that pT3 UCs with extensive parenchymal invasion (defined as invasion deeper than 5 mm) had a prognosis similar to that of pT4 tumors, whereas pT3 UCs without extensive parenchymal invasion (including cases with intraductal spread only) had a prognosis similar to that of pT1/pT2 disease.…”
Section: Discussionsupporting
confidence: 88%
“…2,8,11,12,[14][15][16][17][18][20][21][22][23][24][25]29,[32][33][34] Thus, the identification of independent prognostic variables is an essential step to predict disease evolution, thus aiding surveillance strategies, and also to identify patient subgroups that might benefit from adjuvant cancer therapy. Our study is by far the largest systematic investigation of the impact of pT classification, tumor grade, as well as vascular invasion in patients with both pelvic and ureteral UCs with respect to metastasis-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…18 Our analysis failed to prove the independent prognostic role of histologic grade, which also happened in other large series. 4,[8][9][10] This may have been caused by the lack of a significant difference in survival between patients with grade 1 tumors and grade 2 tumors and by the lack of significant reproducibility in the diagnosis of grade in TCC.…”
Section: Discussionmentioning
confidence: 99%
“…3 The knowledge of prognostic factors for UUT-TCC often is based on studies on the most common bladder TCC, and only a few studies on prognostic factors for UUT-TCC have been published to date, and those sometimes have reported conflicting data. Tumor stage [4][5][6][7][8][9][10][11] and histologic grade 7,11,12 are among the best established prognostic factors; whereas, conversely, the roles of other potentially relevant variables, such as a history of bladder cancer, tumor site, lymphovascular invasion, or multifocality, are less clear. [6][7][8]10,11 A clear knowledge of those prognostic data would be useful for counseling patients after surgery and for identifying those patients with unfavorable cancer-related outcome who may be candidates for future neoadjuvant or adjuvant randomized controlled trials.…”
mentioning
confidence: 99%
“…Mullerad et al 13 informaron de una serie de 129 pacientes y concluyeron que los antecedentes de cá ncer de vejiga tenían un efecto adverso en el pronó stico de los pacientes con TUAUS. Lee et al 14 e Inman et al 15 evaluaron a 112 y 168 pacientes, respectivamente, y hallaron que la supervivencia estaba relacionada tanto con el estadio como con el grado del tumor.…”
Section: Comentariounclassified